GAGASAN ASEAN OPEN SKIES DI INDONESIA DAN KAITANNYA DENGAN KEDAULATAN WILAYAH UDARA INDONESIA - Fajria, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
ASEAN open skies is a form of policy to open the airspace between fellow members of ASEAN countries. ASEAN open skies policy is part of the purpose of the establishment of the ASEAN Economic Community in an effort to boost the economy in the ASEAN region to improve competitiveness in the international arena so that the economy can grow evenly, also improve people's lives, and the main thing is to reduce poverty. ASEAN open skies does offer access to a huge market, huge profits, increase tourist attraction, as well as the flight frequency will increase. The purpose of this thesis namely; First, to determine the relationship or link between sovereignty with the implementation of the ASEAN policy of open skies; Second, to determine the strategy or the Indonesian government's efforts in dealing with the implications of the implementation of the ASEAN open skies policy, especially in terms economic, defense and security. From the research, there are two main things that can be inferred. First, Indonesian airspace sovereignty and the implementation of the ASEAN open skies policy are interrelated. The principle of sovereignty over the airspace is absolutely and fully recognized in the Multilateral Agreements of ASEAN Multilateral Agreement on Air Services that support the ASEAN open skies policy; Second, , Indonesian government's efforts in dealing with the implications of economic, defense and security of the implementation of the ASEAN policy of open skies is to make improvements to the infrastructure at the airport either airport capacity, systems, and technologies that support flight, and the most important is the strengthening of policies and regulations, especially in the field of safety, security and defense, consumer protection, and law enforcement investment.